Treatment of Coronal Fractures of Femoral Condyle - Yonei, Toru; Yamashita, Hideki; Osako, Yu (Orthopedics & Traumatology, 2000)
We report 4 cases of coronal fractures of the femoral condyle. They consisted of 2 men and 2 women whose mean age at the time of injury was 32 years. The cause of injury was motorcycle accident (2 cases), dashboard trauma (1 case), and struck by fallen snow (1 case). Three cases were treated with open reduction and one was performed by cemented TKA. The manipulation for the knee joint was performed on 3 cases, because of the contracture of the joint. We evaluated the clinical results 18.3 months after operation by the Neer's score. The results were excellent in 3 cases and satisfactory in 1 case. In our experiences, the surgical treatment for the coronal fracture of the femur provided satisfactory clinical and radiographical results. But to avoid joint contracture, the range-of-motion exercise should be begun as soon as possible after operation.